2021
DOI: 10.2196/27094
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Professionals’ Experiences With the Use of Video Consultation: Qualitative Study

Abstract: Background The number of remote video consultations between doctors and patients has increased during the last few years and especially during the COVID-19 pandemic. The health care service is faced with rising rates of chronic illness and many patients who are more confident in self-management of their illnesses. In addition, there is an improved long-term outlook for serious conditions, such as cancer, that might require flexibility in everyday life. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Our findings point to ongoing concerns about being able to connect patients to telehealth, and to making decisions that telehealth is not suitable. In agreement with others, telehealth cannot replace face-to-face interactions, when physical examination is required, 20,21 or when vulnerable patients are at risk. There were very few respondents in our study working in inpatient care to be able to assess how telehealth was perceived in acute hospital wards.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Our findings point to ongoing concerns about being able to connect patients to telehealth, and to making decisions that telehealth is not suitable. In agreement with others, telehealth cannot replace face-to-face interactions, when physical examination is required, 20,21 or when vulnerable patients are at risk. There were very few respondents in our study working in inpatient care to be able to assess how telehealth was perceived in acute hospital wards.…”
Section: Discussionsupporting
confidence: 67%
“…15 Furthermore, single healthcare disciplines using telehealth have been examined, for example, geriatrician or memory clinics, 20 cancer care 9 or haematology. 21 First, our results showed that telehealth can fit with usual clinical practises (in ambulatory community settings), when therapeutic rapport has been established, that is, reviews, pre-discharge planning or for educational interactions. Reassuringly, many clinicians (40-50%) and managers (39-60%) in these settings planned to continue or to increase their utilisation of telehealth if no more virus outbreaks occur.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…19 , 23 The GPs in this study reported that the availability of diagnostic tools was reassuring, and this fits with previous research where GPs have reported satisfaction with video consultation but concerns about the lack of physical examination. 24 …”
Section: Discussionmentioning
confidence: 99%
“…The review mainly identified positive experiences with using telehealth [20], which is in line with our findings, wherein most barriers disappeared when the nurses had positive experiences with DA-GSD. A study examining the use of video consultations by doctors also reported the fear of deterioration in the physician-patient relationship, for example, not shaking the patient's hand and having eye contact prevented access to a great deal of important information that the doctors were reluctant to miss [25]. However, they found that they could maintain good contact and assess patients satisfactorily while achieving more relaxed interaction in video consultations [25].…”
Section: The Nurse-patient Relationshipmentioning
confidence: 99%